The influence of job security, burnout and pay satisfaction on turnover intention mediated by job satisfaction in private hospital x (in 2023) - Yansah, Hansens; Palupi Meilani, Yohana Cahya F. (Institute of Computer Science (IOCS), 2024)
Turnover intention is one of the parameters for assessing the effectiveness of human resource management, a high number has the implication that the organization's management system must be improved. A high level of turnover intention in hospitals can disrupt performance and service performance. Based on human resources data at Private Hospital X in West Jakarta, from 2020 - 2023 there is an average turnover rate of 20.43%. This figure is relatively high for turnover. Turnover intention can be influenced by several factors such as Job security, Burnout, and Pay Satisfaction. The cross-sectional method was used to obtain quantitative data from an online questionnaire that was modified based on questions contained in published literature. Data is collected from the entire population of medical personnel. SmartPLS software is used to process data. The research results show that there is a significant positive influence of job security on job satisfaction, a significant negative influence of job satisfaction on turnover intention. Job satisfaction has also been proven to mediate job security and burnout and turnover intention. The results of this research can be a guide for private hospital X which can reduce the turnover intention rate among health workers